NEW LEGAL SOLUTIONS IN THE PROCEDURE FOR THE EXTENSION OF PARENTAL RIGHTS - Stanković, Gordana (Law - Theory and Practice, 2014)
In the paper the author presents the legal-political reasons which have motivated the legislator to change the concept and revise the rules of the special contentious procedure concerning the extension of parental rights in the Law on Amendments to the Law on Contentious Procedure of Republic of Serbia (2014). The author analyzes the compatibility of the new legal solutions to the European legal standards and states that certain new legal solutions do not offer a full and adequate protection of a person this procedure is undertaken against, although they improve it to some extent.